Strengthening the Inclusive Role of Muslim Communities in the Digital Space: Preaching Strategies and Social Media Literacy in the 5.0 Era - Pamuji, Slamet; Iliasu, Samuel Femi (Al-Qalam Institute, 2026)
Digital religious communication increasingly occurs through social media platforms, requiring new strategies to foster inclusive engagement and critical participation. This study aims to examine how inclusive preaching practices, media literacy, and algorithm awareness contribute to strengthening the inclusive role of Muslim communities in digital spaces. The research employed a qualitative approach involving interviews with preachers and community members, observations of digital preaching interactions, and documentation of digital literacy activities. Data were analyzed through thematic interpretation to identify patterns of engagement and critical awareness. The findings show that inclusive dialogic preaching encourages participatory engagement through interactive discussions and direct responses to audience questions. Observations also reveal that media literacy practices such as verifying information sources, comparing scholarly opinions, and delaying content sharing until confirmation enhance critical awareness in online discussions. In addition, documentation of educational activities indicates that algorithm-awareness programs encourage users to diversify their information sources and reduce echo-chamber effects. This study contributes a conceptual integration of dialogic preaching, media literacy, and algorithm awareness as strategies for inclusive digital religious engagement and recommends strengthening community-based digital literacy initiatives.